ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA (K3) AKIBAT PAPARAN DEBU TEPUNG PADA LINI PROSES MIXING INDUSTRI BISKUIT MENGGUNAKAN PENDEKATAN HIRARC DAN FMEA (STUDI KASUS PT XYZ) - Ade Purnama; Abimanyu Abimanyu; Rakay Edhiargo Toyosito (Smart Education, 2026)
Abstract: Flour dust exposure in the mixing process of the biscuit manufacturing industry is a significant occupational hazard that may lead to occupational diseases and workplace accidents if not effectively controlled. This study aims to identify occupational safety and health (OSH) hazards, analyze the level of risk associated with flour dust exposure, prioritize risks using the Failure Mode and Effects Analysis (FMEA) method, and develop risk control recommendations for the mixing area at PT X. The study employed a mixed-methods approach with a case study design. Data were collected through field observations, semi-structured interviews, flour dust concentration measurements, documentation, and company document reviews. Risk analysis was conducted using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method, while improvement priorities were determined using the Risk Priority Number (RPN) derived from FMEA. The results revealed that flour bag opening, raw material loading into the mixer, and the mixing process were the primary sources of flour dust exposure with the highest risk levels. HIRARC identified four high-risk activities and three medium-risk activities. FMEA analysis indicated that inadequate ventilation, workers' exposure to flour dust, and non-compliance with personal protective equipment (PPE) use had the highest RPN values, making them the top priorities for risk control. Recommended control measures include optimizing local exhaust ventilation (LEV), improving the effectiveness of the dust collector system, strengthening administrative controls, providing regular OSH training, and increasing compliance with the use of N95 respirators. These findings are expected to serve as a reference for implementing OSH risk management in the food manufacturing industry. Keyword: occupational safety and health, flour dust exposure, HIRARC, Failure Mode and Effects Analysis (FMEA), mixed methods, biscuit manufacturing industry. Abstrak: Paparan debu tepung pada lini proses mixing industri biskuit merupakan salah satu sumber bahaya yang berpotensi menyebabkan penyakit akibat kerja dan kecelakaan kerja apabila tidak dikendalikan secara efektif. Penelitian ini bertujuan mengidentifikasi potensi bahaya keselamatan dan kesehatan kerja (K3), menganalisis tingkat risiko paparan debu tepung, menentukan prioritas risiko menggunakan metode Failure Mode and Effect Analysis (FMEA), serta menyusun rekomendasi pengendalian risiko pada area mixing PT X. Penelitian menggunakan pendekatan mixed methods dengan desain studi kasus. Data diperoleh melalui observasi, wawancara semi-terstruktur, pengukuran konsentrasi debu, dokumentasi, dan telaah dokumen perusahaan. Analisis risiko dilakukan menggunakan metode Hazard Identification, Risk Assessment and Risk Control (HIRARC), sedangkan prioritas perbaikan ditentukan melalui perhitungan Risk Priority Number (RPN) pada metode FMEA. Hasil penelitian menunjukkan bahwa aktivitas pembukaan karung tepung, penuangan bahan baku ke dalam mixer, dan proses mixing merupakan sumber paparan debu dengan tingkat risiko tertinggi. HIRARC mengidentifikasi empat aktivitas berisiko tinggi dan tiga aktivitas berisiko sedang. Analisis FMEA menunjukkan bahwa ventilasi yang belum optimal, paparan debu terhadap pekerja, dan ketidakpatuhan penggunaan alat pelindung diri memiliki nilai RPN tertinggi. Rekomendasi pengendalian meliputi optimalisasi local exhaust ventilation (LEV), peningkatan efektivitas dust collector, penguatan pengendalian administratif, pelatihan K3 secara berkala, serta peningkatan kepatuhan penggunaan respirator N95. Temuan ini diharapkan menjadi acuan dalam penerapan manajemen risiko K3 pada industri makanan. Kata kunci: keselamatan dan kesehatan kerja, debu tepung, HIRARC, FMEA, mixed methods, industri biskuit.